مفهوم العرفان عند محمد عابد الجابري - Muhammad mukhilis huda (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2018)
This paper aim to describe al-Jabiri’s thought about scientific traditional framework of Arab-Islam especially in ‘irfani’s epistemology. According to Al-Jabiri, that Arab’s logical reasoning can be classified into three major point, bayani, Irfani and burhani. Bayani is a pure Arab’s logical reasoning as it is motivated by cognitive factor to interpret religious texts. Irfani becomes an alternative epistemology for bayani in providing convincing conclusions. While Burhani, is logical reasoning based on rationality. There is a general view about Irfani’s epystemology, that this traditional structure of Arab-Islam framework is a reason factor of Islamic degradation in the world. Al-Jabiri, through his magnum opus about epystemological critics on scientific traditional framework of Arab-Islam describe that this general view about Irfani’s epystemology can be classified into two major point. Irfani as a practice al irfan al mauqifiy and irfani as a theories al irfan an nadzhariy.